The effect of cholesterol and type of fat in the diet on the LDL composition of the African green monkey (Cercopithecus aethiops) - Malan, Maria M.(Maria Magdalena) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.